Pengaruh Gaya Hidup Sehat terhadap Kesehatan Metabolik pada Remaja - Zamroni, Juliandre (Journal of Medical and Health Sciences, 2025)
Adolescence is a critical period in individual development, where lifestyle habits begin to form and can have long-term impacts on health. This study aims to analyze the effect of a healthy lifestyle on metabolic health in adolescents. A healthy lifestyle in this study includes a balanced diet, regular physical activity, good sleep quality, and avoidance of smoking and alcohol consumption. The research method used was a quantitative study with a cross-sectional approach, involving 300 adolescent respondents aged 13–18 years in urban areas. Data were collected through questionnaires and examination of metabolic parameters such as body mass index (BMI), fasting blood glucose levels, blood pressure, and lipid profiles. The results of the analysis showed that adolescents with a healthy lifestyle had a significantly better metabolic profile compared to adolescents with an unhealthy lifestyle (p < 0.05). These findings indicate that the implementation of a healthy lifestyle plays an important role in maintaining metabolic health and preventing the risk of non-communicable diseases in the future. Therefore, early lifestyle interventions need to be encouraged through health education and conducive environmental support.